3D morphometry using automated aortic segmentation in native MR angiography: an alternative to contrast enhanced MRA? - Müller-Eschner, Matthias; Müller, Tobias; Biesdorf, Andreas; Wörz, Stefan; Rengier, Fabian; Böckler, Dittmar; Kauczor, Hans-Ulrich; Rohr, Karl; Tengg-Kobligk, Hendrik von (Cardiovascular Diagnosis and Therapy, 2014)
Introduction: Native-MR angiography (N-MRA) is considered an imaging alternative to contrast enhanced MR angiography (CE-MRA) for patients with renal insufficiency. Lower intraluminal contrast in N-MRA often leads to failure of the segmentation process in commercial algorithms. This study introduces an inhouse 3D model-based segmentation approach used to compare both sequences by automatic 3D lumen segmentation, allowing for evaluation of differences of aortic lumen diameters as well as differences in length comparing both acquisition techniques at every possible location. - Methods and materials: Sixteen healthy volunteers underwent 1.5-T-MR Angiography (MRA). For each volunteer, two different MR sequences were performed, CE-MRA: gradient echo Turbo FLASH sequence and N-MRA: respiratory-and-cardiac-gated, T2-weighted 3D SSFP. Datasets were segmented using a 3D model-based ellipse-fitting approach with a single seed point placed manually above the celiac trunk. The segmented volumes were manually cropped from left subclavian artery to celiac trunk to avoid error due to side branches. Diameters, volumes and centerline length were computed for intraindividual comparison. For statistical analysis the Wilcoxon-Signed-Ranked-Test was used. - Results: Average centerline length obtained based on N-MRA was 239.0±23.4 mm compared to 238.6± 23.5 mm for CE-MRA without significant difference (P=0.877). Average maximum diameter obtained based on N-MRA was 25.7±3.3 mm compared to 24.1±3.2 mm for CE-MRA (P<0.001). In agreement with the difference in diameters, volumes obtained based on N-MRA (100.1±35.4 cm³) were consistently and significantly larger compared to CE-MRA (89.2±30.0 cm³) (P<0.001). - Conclusions: 3D morphometry shows highly similar centerline lengths for N-MRA and CE-MRA, but systematically higher diameters and volumes for N-MRA.